2020
DOI: 10.3389/fpsyg.2020.626330
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude Questionnaire–20 Items (G20): A Cross-Cultural, Psychometric and Crowdsourcing Analysis

Abstract: The use in psychology of crowdsourcing platforms as a method of data collection has been increasing in popularity because of its relative ease and versatility. Our goal is to adapt the Gratitude Questionnaire–20 Items (G20) to the English language by using data collected through a crowdsourcing platform. The G20 is a comprehensive instrument that takes in consideration the different basic processes of gratitude and assesses the construct’s cognitive, evaluative, emotional, and behavioral processes. We test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 38 publications
0
11
0
12
Order By: Relevance
“…Instruments A socio-demographic survey was created for this study (employment status, educational level, marital status, age, and gender). The English adaptation of the Gratitude Questionnaire (G20, Bernabé-Valero et al, 2014) was used in the present study (Bernabe-Valero et al, 2020). This scale has four subscales and 20 items that were rated on a 7-pt scale ("1 = Strongly Disagree" to "7 = Strongly Agree").…”
Section: Design and Samplementioning
confidence: 99%
“…Instruments A socio-demographic survey was created for this study (employment status, educational level, marital status, age, and gender). The English adaptation of the Gratitude Questionnaire (G20, Bernabé-Valero et al, 2014) was used in the present study (Bernabe-Valero et al, 2020). This scale has four subscales and 20 items that were rated on a 7-pt scale ("1 = Strongly Disagree" to "7 = Strongly Agree").…”
Section: Design and Samplementioning
confidence: 99%
“…This is verified in most of the measurement instruments in the list of items. Articles that addressed specific moral virtues empirically observed one or two virtues: appreciation of virtues and their links with status (Bai, Ho, & Yan, 2020), self-consideration and consideration for others (Grappi, Romani, & Bagozzi, 2013), moral courage (Mansur, Sobral, & Islam, 2020), gratitude (Bernabe-Valero, Blasco-Magraner, & García-March, 2020;Gulliford, Morgan, Hemming, & Abbott, 2019;Hudecek, Blabst, Morgan, & Lermer, 2020;Morgan, Gulliford, & Kristjánsson, 2017), gratitude and love (Diessner, Iyer, Smith, & Haidt, 2013), humility (Colombo, Strangmann, Houkes, Kostadinova, & Brandt, 2021;Qin, Liu, Brown, Zheng, & Owens, 2019), integrity (Castro-González, Bande, Fernández-Ferrín, & Kimura, 2019), justice (Beekun, Westerman, & Barghouti, 2005;Beugré, 2012), self-forgiveness (Kim, Volk, & Enright, 2021), respect and responsibility (Manly, Leonard, & Riemenschneider, 2015), good and bad character traits (Jiao, Yang, Guo, Xu, Zhang, & Jiang, 2020), resilience (Lasota, Tomaszek, & Bosacki, 2020) and temperance (Shahab & Adil, 2020).…”
Section: Presentation and Discussion Of Presentation And Discussion O...mentioning
confidence: 99%
“…In this research, a unidimensional measure was chosen to make the questionnaires easier for participants but several studies have found differences in results depending whether a unidimensional or multidimensional measure of gratitude has been used (e.g., Martinez-Cortés and Bernabe-Valero, 2018 ; Bernabé-Valero et al, 2019 ). Future research should address different gratitude conceptions in its nature ( Bernabe-Valero et al, 2020 ) as well as in its cultural conception ( Robustelli and Whisman, 2018 ). On the other hand, gratitude has been shown to be directly related to positive affect and inversely related to negative affect, as previous literature has shown, particularly in times of a pandemic ( Burke et al, 2020 ; Jiang, 2020 ) as well as other historical moments ( Watkins et al, 2006 ; Frias et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…An additional aspect to consider is the instrument employed for the assessment of gratitude based on a unidimensional scale in the current study, which has not allowed us to assess aspects as interesting as gratitude in terms of suffering, but are included in other scales underling the term of gratitude (e.g., the G20 in Bernabé-Valero et al, 2014 ; English adaptation in Bernabe-Valero et al, 2020 ). In other words, this seems particularly suitable for assessing whether people can feel gratitude in situations that generate suffering, such as the ongoing crisis resulting from the current pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation